Darwin e a Sociedade: apresentação - Costa Carvalho, Magda (2014)
Celebrating Darwin: Proceedings of the Symposium Darwin's Mistake and what we are doing to correct it, Ponta Delgada, São Miguel, Açores, September 19-22, 2009.